Impact of malignancy on outcomes in European patients with atrial fibrillation: a report from the ESC-EHRA EURObservational Research Programme in Atrial Fibrillation General Long-Term Registry. (14th October 2021) - Malavasi, V L; Vitolo, M; Proietti, M; Fauchier, L; Marin, F; Nabauer, M; Potpara, T S; Dan, G A; Kalarus, Z; Lane, D A; Lip, G Y H; Boriani, G; et al.
Abstract: Background: Management of patients with atrial fibrillation (AF) and malignancy is a clinical challenge given the paucity of evidence supporting the appropriate clinical management. Purpose: To evaluate the outcomes of patients with active or prior malignancy in a large contemporary cohort of European AF patients. Methods: We analyzed patients enrolled in the ESC-EHRA EORP-AF General Long-Term Registry. We stratified the population into three categories (i) No Malignancy (NoM) (ii) Prior Malignancy (PriorM) and (iii) Active Malignancy (ActM). The primary outcome for this analysis was all-cause death among the three groups. The association between anticoagulant treatment, all-cause death and haemorrhagic events was also evaluated. Results: Among the original 11 096 AF patients enrolled, 10 383 were included in this analysis (median age 71 years (interquartile range [IQR] 63–77, males 59.7%). Of these, 9 597 (92.4%) were NoM patients, 577 (5.6%) PriorM and 209 (2%) ActM. Patients with malignancy (prior or active) had a higher median age, median CHA2DS2-VASc and HAS-BLED scores, compared to patients without malignancy (p<0.001). Lack of anticoagulation (AC) prescription occurred more commonly in ActM (21.5%) as compared with the other groups (PriorM 10.1% vs NoM 12.8%, p<0.001). In case of AC treatment, patients with ActM were treated more frequently with heparins (ActM 8.1% vs PriorM 2.4% vs NoM 2%, p<0.001). After a median follow-up of 730 days [IQR 692–749], 982 (9.5%) patients died. Among all deaths, the proportion of cardiovascular death was different according to the three groups (40.0% in NoM, 26.0% in PrioM and 22.2% in ActM, p=0.002). For all cause-death, Kaplan-Meier analysis showed a progressively higher cumulative risk in the PriorM and ActM groups compared to NoM patients (Figure 1). On multivariable Cox regression analysis, adjusted for CHA2DS2-VASc score, use of AC, type of AF and chronic kidney disease, ActM group was independently associated with a higher risk for all cause death (hazard ratio [HR] 2.90, 95% confidence interval [CI] 2.23–3.76) while PriorM group was not. Among PriorM and NoM patients, multivariable adjusted Cox regression analysis found that the use of any AC was independently associated with a lower risk for all-cause death (HR 0.36, 95% CI 0.19–0.66; HR 0.66, 95% CI 0.54–0.81). No significant association between AC and all-cause death was found for ActM patients. Conclusions: In a large contemporary cohort of European AF patients, active malignancy was found to be independently associated with all-cause death. Use of any AC was associated with a lower risk for all-cause death in patients with no malignancies and with prior malignancies, but with no significant association amongst patients with active malignancies. FUNDunding Acknowledgement: Type of funding sources: Other. Main funding source(s): Since the start of EORP, the following companies have supported the programme: Abbott Vascular Int. (2011–2021), Amgen Cardiovascular (2009–2018), AstraZeneca (2014–2021), Bayer (2009–2018), Boehringer Ingelheim (2009–2019), Boston Scientific (2009–2012), The Bristol Myers Squibb and Pfizer Alliance (2011–2016), The Alliance Daiichi Sankyo Europe GmbH and Eli Lilly and Company (2011–2017), Edwards (2016–2019), Gedeon Richter Plc. (2014–2017), Menarini Int. Op. (2009–2012), MSD-Merck & Co. (2011–2014), Novartis Pharma AG (2014–2020), ResMed (2014–2016), Sanofi (2009–2011), SERVIER (2010–2021), and Vifor (2019–2022).